Investigating pupils group creativity in drama - Teacher trainees fostering a creative classroom environment - Toivanen, Tapio; Halkilahti, Laura (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The use of drama in education can be seen as a method to support pupils creativity. Drama work offers possibilities for creative group processes and aims for deeper conceptual understanding by preparing students to create new knowledge. Having said this, it is difficult to determine whether this is true, and in what way if it is true. This article seeks to answer the following research questions: Can the principles of theatrical improvisation be used as an analytic tool to examine the collaboration and emergence of creative ideas between pupils during drama work? To what degree do teacher trainees succeed in supporting pupils group creativity in drama lessons? The potential complexity and diversity of creative group processes in drama education is challenging for teacher trainees and novice teachers at the beginning of their careers. In this study teacher trainees specializing in drama were observed. Eight lessons were recorded and analyzed using the core principles of improvisation as an analytic tool. The scenes were then interpreted to recognize the characteristics of group creativity (improvisation, collaboration and emergence) defined by Sawyer (2003, 2006, 2012). Both authors analyzed and made their interpretations separately. The findings were compared and the few situations where the authors opinions differed were reconciled by discussion. The research results show that the analysis method based on the principles of improvisation was moderately usable for both exact and more general analysis. Within the restrictions of the case studies, our conclusion is that drama teaching supports pupils group creativity.